Disrupting immune evasion and metabolic vulnerabilities in myeloid malignancies – A therapeutic perspective on Clever-1 - Ylitalo, Arno (fi=Turun yliopisto|en=University of Turku|, 2026)
Relapse and persistence remain major challenges in acute myeloid leukaemia (AML) and myelodysplastic syndromes (MDS). Malignant cells endure not only through clonal genetics but also through support from the marrow niche, where immune restraint and metabolic adaptation coexist. Mitochondrial respiration and lipid utilisation confer survival advantages under therapeutic stress, while intracellular trafficking links immune signalling to mitochondrial metabolism. Clever-1 (STAB1),a scavenger receptor expressed in immunoregulatory myeloid compartments, integrates these processes through endocytic–lysosomal routing. In this PhD thesis, I examine whether Clever-1 functions solely as a niche-level immunoregulatory receptor or also contributes directly to leukaemic cell fitness through cargo routing, mitochondrial lipid handling and bioenergetic adaptation. I characterise Clever-1 expression across malignant myeloid compartments in AML and MDS, spanning immature progenitors and more differentiated myeloid populations, and relate its distribution to differentiation state and immune context. I then investigate cell-intrinsic consequences of Clever-1 targeting. The findings support a role for Clever-1 in endocytic trafficking to mitochondria and selective effects on respiratory organisation. Blockade alters lipoprotein-derived cargo routing, reshapes mitochondrial lipid composition, and reduces respiratory capacity under metabolic constraint, consistent with impaired adaptive flexibility rather than baseline cytotoxicity. To bridge the mechanism with therapeutic relevance, I evaluate antibody-mediated Clever-1 blockade (bexmarilimab) in AML and MDS in ex vivo systems and in an early-phase clinical combination with azacitidine. In this setting, Clever-1 blockade is not primarily a direct cytotoxic therapy but rather a modulator of myeloid state, with target engagement and variable effects shaped by disease context and immune composition. Together, these findings identify Clever-1 as a state-linked trafficking receptor active in both immune and malignant compartments and help define the therapeutic role of Clever-1–directed strategies in AML and MDS.

Immuunivasteen vaimentuminen ja metabolinen alttius myelooisissa verisyövissä – Clever-1 terapeuttisesta näkökulmasta Taudin uusiutuminen ja hoitoresistenssi ovat keskeisiä haasteita akuutissa myelooisessa leukemiassa (AML) ja myelodysplastisissa oireyhtymissä (MDS). Pahanlaatuiset solut säilyvät klonaalisen evoluution lisäksi luuytimen mikroympäristön tuella, jossa aineenvaihdunnallinen sopeutuminen ja immuunivasteen vaimeneminen limittyvät. Mitokondrioissa tapahtuva soluhengitys ja lipidien hyödyntäminen tarjoavat leukemiasoluille selviytymisedun hoitopaineen alla, ja solunsisäiset kuljetusreitit kytkevät immuunisäätelyn mitokondrioiden toimintaan. Clever-1 (STAB1) on immuunivastetta muokkaavissa myelooisissa soluissa ilmentyvä haaskareseptori, joka yhdistää nämä prosessit endosyyttisen kierron kautta. Tässä väitöskirjassa tutkin, toimiiko Clever-1 yksinomaan mikroympäristön immuniteetin säätelijänä vai liittyykö se myös leukemiasolujen vastustuskykyyn kuljetusreittien, mitokondrioiden lipidikäsittelyn ja aineenvaihdunnallisen sopeutumisen kautta. Määritän sen ilmentymistä AML- ja MDS-potilaiden soluissa ja suhteutan havainnot taudin kliiniseen ja biologiseen taustaan sekä tutkin Clever-1:n kohdentamisen solunsisäisiä vaikutuksia leukemiasoluissa. Tulokset osoittavat, että Clever-1 osallistuu lipoproteiiniperäisen materiaalin reititykseen mitokondrioihin ja soluhengityksen säätelyyn osana aineenvaihdunnallista sopeutumista. Sen estäminen muuttaa kolesterolin solunsisäistä reititystä, muokkaa mitokondrioiden lipidikoostumusta ja heikentää hengityskapasiteettia aineenvaihdunnallisen kuormituksen aikana, mikä viittaa heikentyneeseen sopeutumiskykyyn eikä suoraan solunjakautumisen estoon. Mekanismin kliinisen merkityksen arvioimiseksi tutkin myös vasta-ainevälitteistä Clever-1-estämistä AML:ssa ja MDS:ssa sekä ex vivo -kokeissa että varhaisvaiheen kliinisessä tutkimuksessa, jossa potilaat saivat yhdistelmähoitoa atsasitidiinin kanssa. Clever-1-estäminen ei näyttäydy ensisijaisesti sytotoksisena hoitona, vaan luuytimen immunologisen tilan kontekstiriippuvaisena säätelijänä. Tulokset osoittavat, että Clever-1 toimii sekä immuuni- että pahanlaatuisissa soluissa ja tarkentaa Clever-1-kohdennettujen hoitojen terapeuttista roolia AML:ssa ja MDS:ssa.